Parent's reports of lexical and grammatical aspects of toddlers's language in European Portuguese: developmental trends, age and gender differences - Silva, Carla (2017)
The results from a large-scale study on toddlers’ language acquisition in European Portuguese are presented. Toddlers’ lexical and grammatical competencies were assessed using the MacArthur–Bates Communicative Development Inventory: Words and Sentences. The results, based on 3012 reports completed by parents, indicate an increase in the lexical size and on five measures of grammatical development (production of regular morphology, irregular morphology, over-regularizations, mean length of utterances and sentence complexity) across age groups. A main effect of gender was found for lexical size, production of regular and irregular morphology, production of over-regularizations and sentence complexity, with girls obtaining overall higher scores than boys. All lexical and grammatical development measures are positively correlated, even after controlling for age and gender effects. These findings are discussed in terms of their consistency with those obtained for other languages.